KAPASITAS ADAPTIF EKOSISTEM LAMUN (SEAGRASS) DI GUGUS PULAU GURAICI KABUPATEN HALMAHERA SELATAN PROVINSI MALUKU UTARA - Subur, Riyadi; Yulianda, Fredinan; Susilo, Setyo Budi; Fahrudin, Achmad (AgriSains, 2011)
Sea grass bed is an important ecosystem in coastal areas and small islands which plays important and effective roles as a protector of the coastal line and the safety of the mainland area of small islands. Physically, the roles of ecosystem were as erosion prevention, sediment trap and barrier of waves and currents. The existence of these ecosystems in the coastal regions and small islands was an important in enhancing the adaptive capacity of islands against natural disaster because the island serves as a natural protector. The aim of this research was to calculate and assess tha adaptive capacity of sea grass ecosystems growing in the waters of around the small islands in the group of Guraici. The research was conducted on 17 islands located in the group of Guraici islands. Measurement of adaptive capacity of sea grass ecosystem was done by analyzing 6 parameters, namely: Sea Grass Dimension Index (IDLn), Dominant Species of Sea Grass, Sea Grass Coverage Percentage (%), Number of Sea Grass Species, Substrate Type, Distance from The Point of Ecosystem. Sea Grass ecosystem adaptive capacity value was in the range between 0.0-1.0, with capacity of five categories of â€œvery low, low, medium, high and very highâ€. These results indicated that sea grass ecosystem growing in the waters of around the islands in the island of group Guraici had adaptive capacity with values ranging between 0.0-0.59. The ranges of values were distributed into three categories of the adaptive capacities (very low, low and medium). A total of 13 islands had a capacity of sea grass ecosystem â€œmediumâ€, the other three islands with capacity of â€œlowâ€ and one island with a capacity of â€œvery lowâ€.Â Â Â  Key words : Adaptive Capacity, seagrass ecosystem.